2002
DOI: 10.1023/a:1020248700255
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study investigated the effects of supplementing 40 g lauric acid (C12) kg(-1) dry matter (DM) in feed on methane emissions from early-lactating dairy cows and the associated effects on methane, nitrous oxide and ammonia release from the manure during storage. Stearic acid (C18), a fatty acid without assumed methane-suppressing potential in the digestive tract of ruminants, was added at 40 g kg(-1) DM to a control diet. The complete feed consisted of forage and concentrate in a ratio of 1.5:1 (DM basis). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(17 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…DDGS by-products are also rich in fiber complexes with nutrients (such as protein and carbohydrates) that are partially digested in the rumen and gut of the animal. This could increase the amounts of nutrients available for microbial fermentation in the slurry, thus potentially facilitating a compensatory increase of CH 4 production as reported in the study of Külling et al [ 13 ]. Jarret et al [ 14 ] showed that the inclusion of wheat DDGS in pig diets could modify manure quantity and characteristics and thus alter the GHG budget of manure during anaerobic digestion by increasing biogas production.…”
Section: Introductionmentioning
confidence: 93%
“…DDGS by-products are also rich in fiber complexes with nutrients (such as protein and carbohydrates) that are partially digested in the rumen and gut of the animal. This could increase the amounts of nutrients available for microbial fermentation in the slurry, thus potentially facilitating a compensatory increase of CH 4 production as reported in the study of Külling et al [ 13 ]. Jarret et al [ 14 ] showed that the inclusion of wheat DDGS in pig diets could modify manure quantity and characteristics and thus alter the GHG budget of manure during anaerobic digestion by increasing biogas production.…”
Section: Introductionmentioning
confidence: 93%
“…Feeding increased levels of corn silage can also change nutrient digestibility and excretions, which would ultimately affect CH 4 emission potential of manure (Külling et al 2002;Nousiainen et al 2009;Appuhamy et al 2014). In Hassanat et al (2013) and Benchaar et al (2014), increasing corn silage at the expense of alfalfa silage or barley silage linearly increased apparent totaltract digestibility of organic matter (OMd) in Canadian cows, likely resulting in low C excretions in feces and thereby potentially low manure CH 4 emissions.…”
Section: Increasing Corn Silage Content In the Dietmentioning
confidence: 99%
“…The storage depth was 2 m, and the slurry temperature ranged from 23.4°C to 29.3°C in the study by Li et al (2008). On the contrary, Külling et al (2002) found that N 2 O emissions constituted 32% to 61% of GHG emissions during 14-week storage of 40 m 3 of dairy manure at 20°C with a ventilation rate of 0.33 m 3 s -1 . The diverse aeration schemes and storage depths, which affected O 2 availability, contributed to the different patterns of GHG emissions.…”
Section: Contributions Of Individual Ghgs To Overall Global Warming Pmentioning
confidence: 90%